Evolution of Stroke Care at Universiti Sains Malaysia Specialist Hospital, Malaysia (1983–2025): Progress, Challenges, and Future Directions - Abdul Halim, Sanihah; Mafauzy, Mohamad Masykurin; Sapiai, Nur Asma; Mohamad, Nasibah; Ismail, Muhammad Ihfaz; Husin, Mohd Hafizuddin; Md Yusoff, Bazli; Hanafi, Muhammad Hafiz; Mohamad Fauzi, Muhammad Syahir; Wan Mohamad, Wan Syahmi; Ang, Song Yee; Fitzrol, Diana Noma; et al. (Malaysian Journal of Medical Sciences, 2025)
Stroke remains a significant global health burden and is the third leading cause of mortality in Malaysia. Despite advances in the management of acute ischaemic stroke through reperfusion therapies, such as intravenous thrombolysis and endovascular thrombectomy, access to these treatments remains limited in many parts of Malaysia due to high costs and infrastructural constraints. Universiti Sains Malaysia (USM) Specialist Hospital, located in Kelantan state, has transitioned into a comprehensive stroke centre, particularly addressing the needs of suburban and rural populations. USM Specialist Hospital has implemented a multidisciplinary, protocol-driven stroke service that encompasses a rapid triage system, 24-h neuroimaging, reperfusion therapies, a dedicated acute stroke unit, neurocritical care services, cerebrovascular neurosurgery services, and a comprehensive rehabilitation programme. This coordinated stroke management model has improved clinical outcomes, patient survival, and functional recovery rates. The USM Specialist Hospital experience highlights the importance of structured, multidisciplinary stroke care pathways in enhancing treatment access and optimising outcomes, particularly in resource-limited healthcare settings.